Gambaran Keluhan Musculoskeletal Disorder (MSDs) pada Pekerja PDKB PT. PLN (Persero) UP3 Surabaya Selatan - Abdul Jabbar Ridlo; Abdul Hakim Zakky Fasya (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Introduction: Workers in the Work Unit in a State of Voltage (PDKB) are jobs in the maintenance, repair or replacement of insulators and completeness of conductors and other components in the electrical network without turning off the electricity, the number of workers is 10 people. The results of direct observation, there is a potential hazard that poses a risk of occupational disease (PAK), namely musculoskeletal disorders. Musculoskeletal Disorders (MSDs) are complaints of pain in certain body parts experienced by workers. Purpose of this study is to describe the complaints of musculoskeletal disorders (MSDs) suffered by workers. Method: This study used a descriptive quantitative method using the Nordic Body Map (NBM) questionnaire. The purpose of measurement is to use the Nordic Body Map (NBM) questionnaire to determine the level of complaints of musculoskeletal disorders (MSDs) in workeers’ body parts. Results showed that 8 workers had low complaints and 2 workers had moderate complaints. In addition, the parts of the body that often experience pain or pain are the lower neck, upper neck, and waist. Advice that can be given is that workers do stretching before work and take advantage of their break time.